Does citizenship matter? The economic impact of naturalizations in Germany - Max Friedrich Steinhardt (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2008)
The paper analyzes whether citizenship acquisition affects the labor market performance of immigrants in Germany. Up to the present, there is no empirical evidence about this question for Germany. Theoretically, naturalization can increase the productivity by enabling unrestricted access to the labor market. Furthermore, naturalization can increase the labor market opportunities of immigrants by a reduction of administrative costs for the employer. Eventually, the willingness to invest in human capital may increase with the decision to naturalize, which would boost productivity even prior to naturalization. A drawback of most conducted studies for the US, Canada or the Netherlands is that they are based on cross-sectional data. This disables the possibility to control for processes of selfselection within the group of immigrants and to identify the impact channel. In the following the study uses data from the IAB employment sample which allows conducting cross- sectional and panel analysis. The descriptive analysis reveals strong processes of self-selection within the immigrant workforce concerning the naturalization decision. The estimates from a simple OLS estimation indicate a wage premium of naturalized immigrants, whereas the impact for Third Country Nationals has the largest size. Panel estimations show an immediate positive naturalization effect on wages. Furthermore they indicate accelerated wage growth in the years after the naturalization. It is a question of integration policy whether this passport advantage in the assimilation process is intended.
Keywords: J31; J61; J68; 330; Naturalization; economic impact; self-selection; socioeconomic integration